Individual differences in the perceptual span during reading: Evidence from the moving window technique - Choi, Wonil; Lowder, Matthew W.; Ferreira, Fernanda; Henderson, John M. (Attention, perception & psychophysics, 2015)
We report the results of an eye tracking experiment that used the gaze-contingent moving window technique to examine individual differences in the size of readers’ perceptual span. Participants read paragraphs while the size of the rightward window of visible text was systematically manipulated across trials. In addition, participants completed a large battery of individual-difference measures representing two cognitive constructs: language ability and oculomotor processing speed. Results showed that higher scores on language ability measures and faster oculomotor processing speed were associated with faster reading times and shorter fixation durations. More interestingly, the size of readers’ perceptual span was modulated by individual differences in language ability but not by individual differences in oculomotor processing speed, suggesting that readers with greater language proficiency are more likely to have efficient mechanisms to extract linguistic information beyond the fixated word.